Morphological Awareness of The Fourth Semester Students of English Department : English - Giyatmi; Purwani Indri Astuti; Sihindun Arumi (Journal of English Development, 2024)
Morphological awareness that greatly influences in language learning means an individual's ability to recognize the internal structure of words. English Department students should have better morphological awareness than non-English Department students because as an English teacher to-be, hopefully they can hone their future students' morphological awareness to help them learning English. This research aims to determine the morphological awareness of the fourth semester students of English Department. This is a descriptive qualitative research observing the English Department students' morphological awareness. The population of this research is the fourth semester students of English Department 2022/2023 academic year. The data used is the score of Morpheme Identification Awareness Test (MIAT) and Morpheme Structure Awareness Test (MSAT). The data are gained by having Morphological Awareness Test consisting of MIAT and MSAT. Therefore, the instrument used is a test. The results of the test are analyzed to find the classification of morphological awareness. Having analyzed the data, the writers found that the average of morpheme identification awareness test of the students is 66 (Sufficient) and that of morpheme structure awareness test is 85 (Good). Therefore, the writers concluded that the morphological awareness of the fourth semester students of English Department belongs to Good (74.5)